Extranjeros in Amerika - Gesetzgebung und bourbonische Reformpolitik - Biersack, Martin (Anuario de Historia de América Latina, 2017)
The article examines the impact of the early Bourbon reforms on the politics towards foreigners in Spanish America. It reconstructs two of the main governmental instruments to control migration: naturalization procedures and legislation on foreigners. Regarding the naturalization practice, the article describes the changes it experienced during the eighteenth century, such as the non-application of the Composición and the newly introduced instrument of the Cartas de tolerancia. Legislation aimed to close gaps by which foreigners so far had tried to avoid an expulsion from America. Both, changes in naturalization procedures and legislation finally should strengthen the king’s sovereignty concerning the legal admission of foreigners. Nevertheless, in practice the American authorities still held many resources to tolerate foreigners by their own.
Keywords: Citizenship; Naturalization; Composición; Migration; Foreigners; Spanish-American History 1700-1767